The Ca2+-ATPase inhibition potential of gold (I, III) compounds - Fonseca, Custódia (2020)
The therapeutic applications of gold are well-known for many centuries. The most used gold compounds contain Au(I). Herein, we report, for the first time, the ability of four Au(I) and Au(III) complexes, namely dichloro (2-pyridinecarboxylate) Au(III) (abbreviated as1), chlorotrimethylphosphine Au(I) (2), 1,3-bis(2,6-diisopropylphenyl) imidazole-2-ylidene Au(I) chloride (3), and chlorotriphenylphosphine Au(I) (4), to affect the sarcoplasmic reticulum (SR) Ca2+-ATPase activity. The tested gold compounds strongly inhibit the Ca2+-ATPase activity with different effects, being Au(I) compounds2and4the strongest, with half maximal inhibitory concentration (IC50) values of 0.8 and 0.9 mu M, respectively. For Au(III) compound1and Au(I) compound3, higher IC(50)values are found (4.5 mu M and 16.3 mu M, respectively). The type of enzymatic inhibition is also different, with gold compounds1and2showing a non-competitive inhibition regarding the native substrate MgATP, whereas for Au compounds3and4, a mixed type of inhibition is observed. Our data reveal, for the first time, Au(I) compounds with powerful inhibitory capacity towards SR Ca(2+)ATPase function. These results also show, unprecedently, that Au (III) and Au(I) compounds can act as P-type ATPase inhibitors, unveiling a potential application of these complexes.